The Treatment of Acquiescence and the Factorial Structure of the Brief Resilience Scale (BRS) in Mexican and Chilean University Students - Hidalgo-Rasmussen, Carlos Alejandro; González-Betanzos, Fabiola (Anales de Psicología / Annals of Psychology, 2018)
The aim of this study was to evaluate the factorial structure of the Spanish version of Brief Resilience Scale (BRS) considering the acquiescence bias (tendency to respond for one side of the scale) in a large sample of Mexican university students (N=1572) and a cross-validation of the same models with Chilean university students (N=1345). Six models are compared using Factorial Confirmatory Analysis, in three of them different method factors are used to treat acquiescence. The results show that in Mexican students a better fit is observed in these models especially in the model of a general factor called Resilience that has two factors of method (c2 =32.22, gl=7, p < .001, NFI= .98, GFI = .99, RMSEA = .048), while in the Chilean students the models that do not use factors to deal with acquiescence are the ones of better fit, specifically the models of two correlated factors and also the model to which a factor of second order is added (c2 =34.66, gl=8, p < .001, NFI= .98, GFI = .99, RMSEA = .05). The acquiescence affects each of the samples used differently, so it is important to analyze the presence of response styles associated with acquiescence.